Effect of income inequality on quality of tertiary education Should professors from Cambridge thank to Robin Hood? - Jedlička, Roman; Stroukal, Dominik, 1987-; Nikolovová, Pavla, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
Many factors influence quality of higher education. Current research mostly works with economic factors (GDP, higher education expenditures etc.). However, there are also publications that examine an impact of sociological aspects on quality of higher education. My research examined the impact of income inequality on quality of tertiary education. In the analysis of socioeconomic data of 76 countries I have proven that there is no linear relationship between income inequality and quality of tertiary education. According to my results the size of population, GDP per capita and being English speaking country are main drivers of quality of tertiary education. Modified model without outliers also shows that there is a positive effect of R&D expenditures on quality of tertiary education.
Vedoucí práce: Dominik Stroukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses